(untitled) (World Bulletin of Social Sciences, 2022)
Today, the formation communicative competence in a foreign language is one of the main goals of teaching a foreign language at early stages of studying at academic lyceums in our country. There are quite a lot of methods for the formation of language skills, the formation of communicative competencies based on modern information and communication technologies. This article discusses identifying theoretical issues including studying psychological and pedagogical factors of learning a foreign language such as students’ motivation to use multimedia technologies in learning a foreign language, both English teachers and students’ competence in the use of ICT and selecting a series of tasks for the formation of communicative competence based on language multimedia programs